TINJAUAN YURIDIS KASUS KEBAKARAN LAPAS KELAS 1 TANGERANG DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA MENURUT UU NO. 39 TAHUN 1999 TENTANG HAS ASASI MANUSIA: Fire Case at Class 1 Prison in Tangerang in Human Rights Perspective - MAULANA ARIF HIDAYATULLAH BARUS; MAULANA ARIF HIDAYATULLAH; Tri Sulistyowati (Reformasi Hukum Trisakti, 2024)
The safety guarantee of the right to life for prisoners in correctional institutions (“lapas”) is often neglected, even though it is the responsibility of the state.  One of the cases that occurred was the alleged negligence of government officials in the management of facilities and infrastructure in prison, such as the fire that occurred in Correctional Institutions Class 1 Tangerang on September 8, 2021. The problems of this article are:  whether there is a violation of human rights in the case of fire in Correctional Institutions Class 1 Tangerang? This article is a normative legal research, descriptive in nature, using secondary data, and deductive inference. The Result and conclusion obtained is that there was a violation of human rights due to the negligence of several prison officers which then caused a fire and resulted in casualties. Related to the case, four prison officers were charged under Articles 359 and 188 of the Criminal Code with a prison sentence of up to five years. Improvement and revitalization of prisons are also needed so that the safety of prisoners in prison can be better guaranteed.